Looking beyond the impact of energy prices: What drives trend inflation in Denmark? - Renato Faccini; Pernille Valentin Borgensgaard (Danmarks Nationalbank, 2022)
Before the pandemic, wage and price inflation remained low in Denmark and other advanced economies, despite falling unemployment rates. We attribute the subdued inflation to low competition among firms to hire employed workers. This same force may continue to constrain inflation once the current rise in energy and commodity prices has been passed through to consumer prices.
Keywords: 330; Inflation; wages and prices